A systematic review and meta-analysis study on the factors affecting sports psychology, athletic performance and physical activity - Wang, W.; Chen, H. (Medicina dello Sport, 2024)
INTRODUCTION: Sports excellence is not only about physical abilities, but also about psychological robustness, cognitive skills, and behaviors. Understanding these aspects is vital in optimizing performance levels, injury prevention, increasing motivation to sports, and long-term physical activity. This study aimed to provide a meta-analysis study on the factors influencing sports psychology, athletic performance, and physical activity.